LANGUAGE AND LEGAL IMPLICATIONS IN INSURANCE POLICIES - Omonov Turgunboy (American Journals, 2023)
This article delves into the intricate intersection of language and legal implications within insurance policies. Examining the linguistic nuances and legal intricacies of insurance documents, this study explores the profound impact of language on policyholders’ rights, obligations, and interpretations of coverage. Through the analysis of legal terminology, contract law principles, and linguistic constructs, this research sheds light on the challenges and opportunities in ensuring clarity, fairness, and effectiveness in insurance policies.
Keywords: Language; Legal Implications; Insurance Policies; Contract Law; Linguistic Nuances; Policy Interpretation.